Induced Spawning of Giant Gouramy Osphronemus gouramy Lac. by Ovaprim - Arfah, H.; Maftucha, L.; Carman, O. (Indonesian Society of Scientific Aquaculture (ISSA), 2006)
Spawning season of giant gouramy Osphronemus gouramy Lac is not happen continuously through the year so the supply of fry is not enough for fulfilling the demand. Artificial fertilization will be useful to produce larvae and fry at out of their spawning season. In this study, three dose levels of ovaprim, i.e. 0.6, 0.7 and 0.8 ml/kg fish were used to induce spawning of giant gouramy. Parameters observed were the width of abdomen, number of eggs, fertilization rate, hatching rate, and survival rate of larvae. The results of this study showed that average of fertilization rate reached 4.3% with number of eggs fertilized was 50 eggs, hatching rate 78.5% with number of larvae hatched was 43 larvas. Average of larvae survived until the end of experiment was 35, with average survival rate was 76.82%. Based on the achievement in this study, induced spawning by ovaprim could be applied to giant gouramy, although the success is still very low. Keywords: giant gouramy, Osphronemus gouramy Lac., artificial spawning, ovaprim. ABSTRAK Musim pemijahan ikan gurame Osphronemus gouramy Lac. bukan sepanjang tahun sehingga pasokan benih tidak selalu tersedia dalam jumlah yang cukup. Pemijahan buatan memungkinkan untuk memperoleh suplai larva dan benih di luar musim pemijahannya. Pada penelitian ini tiga tingkatan dosis ovaprim, yaitu 0,6 ml/kg, 0,7 ml/kg, 0,8 ml/kg ikan digunakan untuk merangsang pemijahan ikan gurame. Parameter yang diamati adalah lebar perut, jumlah telur, derajat pembuahan telur (Fertilization Rate), derajat penetasan telur (Hatching Rate) dan tingkat kelangsungan hidup larva (Survival Rate). Rata-rata derajat pembuahan telur ikan gurame yang dipijahkan secara buatan mencapai 4,30% dengan jumlah telur yang dibuahi sebanyak 50 butir, sedangkan derajat penetasan rata-rata adalah 78,50 % dengan jumlah rata-rata telur yang menetas sebanyak 43 butir. Rata-rata jumlah larva hidup pada akhir masa pemeliharaan adalah 35 ekor, dengan rata-rata SR sebesar 76,82%. Berdasarkan hasil penelitian ini dapat disimpulkan, bahwa ransangan pemijahan pada ikan gurame menggunakan ovaprim dapat dilakukan, meskipun tingkat keberhasilannya masih sangat rendah. Kata kunci: gurame, Osphronemus gouramy Lac., pemijahan buatan, ovaprim.